SUS ADMINISTRATION MANAGEMENT AND CHALLENGES (REMUNOM, 2023)
It is known that the Unified Health System (SUS) is the widest public system that deals with health in the world and, therefore, managing it becomes a challenge for its managers. Faced with this reality, this article carried out an analysis of the SUS management system and the barriers encountered for the effectiveness of its processes. It is a relevant topic, since the whole society benefits when the SUS is managed effectively. This study aims to analyze the current SUS management system, identifying possible challenges that exist in it, through bibliographical research. As a result, there was first a characterization of the SUS and its management. The challenges encountered were also identified. In conclusion, it can be verified that there is, in theory, an effective management of the SUS, with broad legislation to seek this good administration. However, in practice there are numerous barriers, which need to be overcome to bring about improvements in the management of the SUS.